An Easy Introduction to XML Publishing-Part 3 of a Five-Part Series Developing a new publishing systems. - Bartlett, PC (SOA webservices journal.)
In Part I of this series we discussed some of the key problems of capturing and sharing information and in Part 2 we looked at the critical components of a solution: modularization, automation and XML